2015
DOI: 10.1089/ees.2014.0459
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Surface Spills of Cold Lake Blend Diluted Bitumen Treated with Dispersant and Mineral Fines in a Wave Tank

Abstract: Cold Lake Blend (CLB) diluted bitumen (dilbit) was used to evaluate the fate and transport of preweathered (6.2% w/w) dilbit under environmental conditions both in spring (seawater temperature 8.5°C -1.3°C and salinity 27.7 -1.6 practical salinity units [psu]) and in summer (seawater temperature 17.0°C -2.6°C and salinity 26.8 -2.4 psu). The following oil spill treatments were considered: no treatment, dispersant alone, mineral fines (MF) alone, and dispersant + MF. The aim was to determine their influences on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The tank dimensions are 30 m long, 0.6 m wide and 2.0 m high, with a typical water level of 1.5 m ( Figure 1). The tank is equipped with a series of manifolds to generate a more or less uniform current along the wave propagation direction; hence, the label flow-through system has been used to evaluate dispersant effectiveness of fresh and weathered crude oils [4,5,8,[14][15][16]. The hydrodynamics of the various wave types generated in the wave tank facility has been characterized in prior works [17,18].…”
Section: Oil Types and Characterizing The Chemical Composition And Phmentioning
confidence: 99%
See 2 more Smart Citations
“…The tank dimensions are 30 m long, 0.6 m wide and 2.0 m high, with a typical water level of 1.5 m ( Figure 1). The tank is equipped with a series of manifolds to generate a more or less uniform current along the wave propagation direction; hence, the label flow-through system has been used to evaluate dispersant effectiveness of fresh and weathered crude oils [4,5,8,[14][15][16]. The hydrodynamics of the various wave types generated in the wave tank facility has been characterized in prior works [17,18].…”
Section: Oil Types and Characterizing The Chemical Composition And Phmentioning
confidence: 99%
“…Two particle size counters (Laser In-situ Scattering Transmissometry (LISST)-100X, Sequoia Scientific, Inc., Bellevue, WA, USA) were employed during the experiments, one at 1.2 m and another at 12 m downstream of the oil release point and both at a depth of 0.45 m ( Figure 1). Particle size (2 to 500 µm) distributions were recorded at 2.0 s intervals for 1 h per experiment as in previous studies [4,8,10,[14][15][16].…”
Section: Wave Tank In Situ Measuring Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, whether bitumen products will float or sink, their response to evaporation, solar exposure, and mixing with water and sediment are determined by their chemical composition (eg King et al . ), which is largely unknown (Crosby et al . ) but is the most fundamental requirement for understanding the consequences of bitumen spills (Chang et al .…”
Section: Sources Of Ecological Impactmentioning
confidence: 99%
“…Due to the paucity of publicly available research on the effects of diluted bitumen on marine biota, we assigned the highest research priority to this source (Table 1 and Figure 3). In fact, whether bitumen products will float or sink, their response to evaporation, solar exposure, and mixing with water and sediment are determined by their chemical composition (eg King et al 2015), which is largely unknown (Crosby et al 2013) but is the most fundamental requirement for understanding the consequences of bitumen spills (Chang et al 2014). For example, one laboratory study on the behavior of diluted bitumen products in saltwater found that dilbit floated in a similar fashion to conventional oil in water free of sediment, but sank and dispersed as "tarballs" when mixed by wave action with fine seawater sediments (Environment Canada 2013).…”
Section: Bitumen In the Environmentmentioning
confidence: 99%